The mediating role of purchasing duration in the effect of social media dependency on consumer purchasing behavior: Comparison of india and Turkey - Rawal, Yashwant Singh; Baser, Mirac Yucel; Batabyal, Debasish; Durmaz, Yakup (Pacıfıc Inst Management, 2024)
This study aims to investigate the mediating role of purchase duration in the effect of social media use on online consumer purchasing behavior. As social media has been gaining increasing importance worldwide, becoming, it has also been changing shopping habits in almost all countries. With so many consumers spending more time online than ever before, it is important to understand how long it takes them to make a purchase and which factors are involved in their decision-making process. More specifically, this study examines the relationship between social media dependency and consumer purchasing behavior, focusing on the mediating effect of purchase duration. A study involving 329 individuals from India and 204 from Turkey was conducted, and the data was analyzed using PLS structural equation modeling. The results indicated that social media dependency positively influences consumer purchasing behavior. Also, the study exhibits that purchase duration mediates the relationship between social media dependency and consumer purchasing behavior.
Keywords: Consumer Purchasing Behaviour (COPB); Purchase decision; Social Media Dependency; SEM-PLS; Mediating role